Digital Pain Drawings: Assessing Touch-Screen Technology and 3D Body Schemas. - Boudreau, Shellie A.; Badsberg, Susanne; Christensen, Steffan W.; Egsgaard, Line L. (Clinical Journal of Pain, 2016)
Objectives: To assess the consistency and level of agreement between pain drawings collected on (1) paper and a personal computer tablet; and (2) between a 2-dimensional (2D) line drawing and 3-dimensional (3D) body schema.Materials and Methods: Pain-free participants (N=24) recreated a premarked "pain" area from a 2D line drawing displayed on paper onto paper or tablet, and individuals with chronic neck pain (N=29) expressed their current pain on paper and tablet. A heterogeneous group (N=26) was recruited from cross-disciplinary pain clinic and expressed their pain on a 2D line drawing and a 3D body schema, as displayed on a tablet, and then completed an user-experience questionnaire.Results: Pain drawings showed moderate to high level of consistency and a high level of agreement for paper and tablet and between 2D line drawing and 3D body schema. A fixed bias (-1.0042, P<0.001) revealed that pain areas were drawn slightly smaller on paper than on tablet, and larger on the 2D than the 3D body schema (-0.6371, P=0.003), as recorded on a tablet. Over one-third of individuals with chronic pain preferred and/or believed that the 3D body schema enabled a more accurate record; 12 believed they were equal, and 3 preferred the 2D line drawing.Discussion: Pain drawings recorded with touch-screen technology provide equal reliability to paper but the size of the drawing slightly differs between the platforms. Although, 2D line drawings and 3D body schemas were similar in terms of consistency and reliability, it remains to be confirmed whether 3D body schemas increase the accuracy and precision of pain drawings.